2020
DOI: 10.3892/etm.2020.8429
|View full text |Cite
|
Sign up to set email alerts
|

Addition of dexmedetomidine to epidural morphine to improve anesthesia and analgesia for cesarean section

Abstract: The aim of the present study was to evaluate the effectiveness and safety of the combination of epidural dexmedetomidine and morphine in providing anesthesia during cesarean surgery and analgesia for post-cesarean pain relief when added to epidural ropivacaine. A total of 80 females at term scheduled for elective cesarean delivery were randomly assigned to two groups (n=40/group): In the morphine group (group M), patients received an epidural injection of 0.75% ropivacaine (12 ml) and morphine (2 mg) for surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
3
12
0
1
Order By: Relevance
“…The two groups of patients received routine oxygen inhalation by mask during the operation. After the operation, the intravenous self-control pump was turned on, and the two groups had the same formula [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The two groups of patients received routine oxygen inhalation by mask during the operation. After the operation, the intravenous self-control pump was turned on, and the two groups had the same formula [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Welker et Al [37] found a visceral pain rate of 17% when EPA was performed with bupivacaine in lateral decubitus position. E. Bjornestad and coworkers [29] found 20% and 30% of visceral pain in their study with epidural lidocaine and epidural 2-chloroprocaine respectively, while Yicheng Yang and colleagues [38] found an intraoperative pain incidence ranged at 70% and 47.5% respectively in epidural ropivacaine-morphine and epidural ropivacaine-morphinedexmedetomidine. It is actually known that epinephrine has some properties of antinociceptive and enhances the duration of analgesia used together with LAs [39,40] .…”
Section: Discussionmentioning
confidence: 95%
“…Our results are similar to those of Chantal T. Crochetière and coworkers [32] . Other researchers have considered abnormal Apgar score or acidosis with Apgar score < 7 [27,38,47,48] . In their study for epidural anesthesia, comparing ropivacaine and bupivacaine effects for scheduled CS, Sandra Kampe et al [27] found some cases of neonates with Apgar score less than 7.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, as a highly selective α‐2 adrenergic receptor agonist, can effectively attenuate noradrenergic effects by inhibiting the binding of α‐2 presynaptic adrenergic receptors to the locus coeruleus in the brain. Dexmedetomidine can be administered both intravenously and intrathecally in obstetric anaesthesia 16–18 to optimize anaesthesia, reduce intraoperative stress and adverse reactions and ensure the safety of the infant and breastfeeding 7,19 . In addition, it has certain organ protective effects in subjects with preeclampsia, pulmonary hypertension in pregnancy and hyperthyroidism 20–23 .…”
Section: Discussionmentioning
confidence: 99%